Characteristics of Ethylene Biosynthesis-Inducing Xylanase Movement in Tobacco Leaves - Sharon, Amir (1992)
(125)I-Labeled ethylene biosynthesis-inducing xylanase (EIX) was used to study the movement of this protein in tobacco (Nicotiana tabacum) tissues. A biologically active (125)I-labeled EIX was obtained using chloramine-T as the oxidizing agent. Labeled EIX was detected in the far most edges of the leaf 5 min after it was applied to the petiole of a detached leaf. EIX was distributed uniformly throughout the leaf, including the mesophyll area within 5 to 15 min, after which there was only little change in the distribution of radioactivity in the leaf. (125)I-Labeled EIX was extracted from treated leaves, and EIX translocation in the leaf was blocked by preincubation of labeled EIX with anti-EIX antibodies, indicating that the intact peptide moves in the leaf. Injection of anti-EIX antibodies into the intercellular spaces of the leaf mesophyll prevented induction of necrosis by EIX, suggesting the mesophyll as the site of EIX action. EIX was translocated both to upper and lower parts of the plant when applied to a whole plant through the petiole of a cut leaf. Radioactivity was found in all leaves and in the stem, although some leaves accumulated much more EIX than others; EIX was not found in the roots. There was no difference between the accumulation pattern of EIX in fresh and ethylene-treated leaves or between sensitive (Xanthi) and insensitive (Hicks) tobacco cultivars. These data support the hypothesis that intact EIX protein is translocated to the leaf mesophyll, where it directly elicits plant defense responses.